2004
DOI: 10.1051/0004-6361:20041365
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Mg$\mathsf{_{2}}$SiO$\mathsf{_{4}}$ and amorphous Mg-bearing silicate grain formation by coalescence and growth

Abstract: Abstract.A novel method for producing MgO and SiO 2 smokes was developed. Mg-bearing silicate grain formation using the coalescence and growth of MgO and SiO 2 grains was carried out in our laboratory. It becomes evident that single and poly crystalline Mg 2 SiO 4 (forsterite) and amorphous Mg-bearing silicate grains can be produced by the coalescence and growth of MgO and SiO 2 grains. This result suggests that the observed crystalline Mg 2 SiO 4 grains and amorphous Mg-bearing silicate particles in Red Super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…The experimental setup for producing MgO and SiO 2 grains and the system for bringing about their coalescence were the same as those used in a previous work (Kamitsuji et al 2005). The evaporation chamber was a glass cylinder of 17 cm diameter and 30 cm height, covered with stainless steel on top and connected to a high-vacuum exhaust through a valve at its bottom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup for producing MgO and SiO 2 grains and the system for bringing about their coalescence were the same as those used in a previous work (Kamitsuji et al 2005). The evaporation chamber was a glass cylinder of 17 cm diameter and 30 cm height, covered with stainless steel on top and connected to a high-vacuum exhaust through a valve at its bottom.…”
Section: Methodsmentioning
confidence: 99%
“…We have also suggested that single crystalline Mg 2 SiO 4 , polycrystalline Mg 2 SiO 4 , and amorphous Mg-bearing silicate grains are produced by the coalescence of MgO and SiO 2 smoke grains (MgO-SiO 2 system) (Kamitsuji et al 2005). This finding suggests that the observed crystalline Mg 2 SiO 4 grains and amorphous Mg-bearing silicate grains in Red Super Giant (RSG), Asymptotic Giant Branch (AGB), post-AGB and planetary nebula (PNe) could be produced by the coalescence and growth of MgO and SiO 2 grains.…”
Section: Introductionmentioning
confidence: 95%
“…In contrary to many other refractory metal-silicon-oxygen systems, Mg can form stable phases with Si and O, such as Mg 2 SiO 4 and MgSiO 3 . It has been reported that Mg 2 SiO 4 grains can be produced by the coalescence of MgO and SiO 2 grains [16]. In addition, Mg 2 SiO 4 and MgSiO 3 also would be formed using Mg and Si substrate under the appropriate partial pressure of oxygen [15].…”
Section: Fig 4: Tem Images and Corresponding Fft Patterns Of The Nanmentioning
confidence: 99%
“…To explain how cometary silicates crystallize under pressure in volatile interstellar ice in their parent comets, we experimentally demonstrated the possibility of a chemical reaction-driven crystallization , which is called nonthermal crystallization (Yamamoto and Chigai, 2005;Yamamoto et al, 2010), using laboratory-synthesized amorphous Mg-bearing silicate grains (Kamitsuji et al, 2005). If the crystalline grain surface is covered with an amorphous silicate layer, the crystallization of the amorphous silicate layer may be different due to the different rates of thermal diffusion between amorphous and crystal layers, as observed during the crystallization of a carbon layer covering Pt clusters (Shintaku et al, 2006;.…”
Section: Introductionmentioning
confidence: 99%